Method in the Madness: Finding the Right Project Management Fit for Industrial Investment Projects - A Case Study - Eliasson,Arvid; Gustafsson,Linus (2025)
Project management is a widely discussed subject in both project management literature and academia. Still, organizations struggle with the complexity of managing projects effectively, especially in complex industrial environments. This thesis investigates investment projects at ABB in a single case study to explore which methodology is appropriate for investment projects within the organization. Qualitative data was collected through interviews with project managers, factory workers and governance owners at different units of the company. The data was analyzed using the Gioia methodology and synthesized with existing academic literature to provide both company-specific recommendations and insights that are more generalizable to similar organizations. The results from the interviews, supported by literature, are that a hybrid framework based on a predictive framework with adaptive features is appropriate. These features, such as continuous improvement and tool usage, complement the predictive framework in investment projects. It is also clear that the methodology should be tailored to the organization, the type of project and the specific project. Additionally, the thesis highlights the previously overlooked importance of supplier communication in investment projects and the transfer of project leadership. To complement these insights the authors developed a tailored framework, methodology and processes for ABB Electrification Smart Power in Västerås to provide guidance and practical examples on how the insights could be implemented. Ultimately, this study supports a tailored hybrid methodology for managing investment projects in an industrial environment.
Keywords: project management methodology; investment projects; hybrid framework; tailoring; project management; projektledningsmetodik; investeringsprojekt; hybridramverk; skräddarsy; projektledning